2013
DOI: 10.1007/s12630-013-9989-4
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol prevents morphine-induced pruritus without increasing pain and other side effects: a systematic review of randomized controlled trials

Abstract: Purpose Pruritus is a frequent adverse event after administration of morphine. Butorphanol has been used to prevent morphine-induced pruritus, but its efficacy is still controversial. The aim of this systematic review was to evaluate the efficacy of using butorphanol to prevent morphine-induced pruritus. Source We searched PubMed, Cochrane Library, EMBASE, and China's BioMedical Disc for full reports of randomized controlled trials that compared the use of butorphanol with either placebo or no treatment for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…These data indicated that nalfurafine can be used for long‐term treatment of intractable pruritus with minimal concern regarding the risk of dependence (Nakao et al , ). All other mixed μ/κ receptor agonists in clinical use, such as butorphanol, nalbuphine and pentazocine, alleviate morphine‐induced pruritus; however, only butorphanol is used to treat chronic pruritus (Du et al , ). Dihydroetorphine is one of the most potent analgesic opioids known, with up to 12‐fold higher potency than morphine.…”
Section: Rationale For the Development Of Multi‐targeting Opioid Ligandsmentioning
confidence: 99%
“…These data indicated that nalfurafine can be used for long‐term treatment of intractable pruritus with minimal concern regarding the risk of dependence (Nakao et al , ). All other mixed μ/κ receptor agonists in clinical use, such as butorphanol, nalbuphine and pentazocine, alleviate morphine‐induced pruritus; however, only butorphanol is used to treat chronic pruritus (Du et al , ). Dihydroetorphine is one of the most potent analgesic opioids known, with up to 12‐fold higher potency than morphine.…”
Section: Rationale For the Development Of Multi‐targeting Opioid Ligandsmentioning
confidence: 99%
“…Nevertheless, several studies have shown a decreased incidence of pruritus without other side effects when butorphanol was administered with morphine epidurally in pediatric patients (Bailey et al 1994; Gunter et al 2000; Lawhorn et al 1995; Lawhorn and Brown 1994). A recent systematic review also indicates the potential benefits of using butorphanol to prevent neuraxial morphine-induced itch and decrease pain intensity and postoperative nausea and vomiting without increasing other side effects (Du et al 2013). Importantly, a pharmacological study demonstrates that butorphanol’s partial agonist actions at both MOP and KOP sites contribute to its antipruritic actions, i.e., low-efficacy ligands antagonize high-efficacy ligand’s action in producing itch sensation (Lee et al 2007).…”
Section: Pharmacological Antagonism By Opioid-related Ligandsmentioning
confidence: 99%
“…Pentazocine also had a lower pruritus recurrence rate [20]. A recent systematic review on the effectiveness of butorphanol included 16 trials, and 795 patients were analyzed [21]. Butorphanol reduced opioidinduced pruritus either by intravenous or epidural routes with an RR of 0.22 (95% CI 0.10 to 0.45) and RR 0.24 (95% CI 0.16 to 0.36), respectively.…”
Section: Pentazocine and Butorphanolmentioning
confidence: 99%